Three Problems in Convergence Theory - Wojciechowski, Jerzy (Topology Proceedings, 2022)
In this note, we prove that the class of paratopologies is simple and that under the assumption that the measurable cardinals form a proper class, the class of hypotopologies is not simple. Moreover, we provide an example of a Hausdorff convergence with idempotent set adherence (subdiagonal convergence) that is not weakly diagonal.